Acute rimonabant treatment promotes protein synthesis in C2C12 myotubes through a CB1‐independent mechanism. Issue 4 (3rd September 2020) - Le Bacquer, Olivier; Lanchais, Kassandra; Combe, Kristell; Van Den Berghe, Loïc; Walrand, Stéphane
Abstract: Sarcopenia is an age‐related loss of muscle mass associated with changes in skeletal muscle protein homeostasis due to lipid accumulation and anabolic resistance; changes that are also commonly described in obesity. Activation of the endocannabinoid system is associated with the development of obesity and insulin resistance, and with the perturbed skeletal muscle development. Taken together this suggests that endocannabinoids could be regulators of skeletal muscle protein homeostasis. Here we report that rimonabant, an antagonist for the CB1 receptor, can prevent dexamethasone‐induced C2C12 myotube atrophy without affecting the mRNA expression of atrogin‐1/MAFbx (a marker of proteolysis), which suggests it is involved in the control of protein synthesis. Rimonabant alone stimulates protein synthesis in a time‐ and dose‐dependent manner through mTOR‐ and intracellular calcium‐dependent mechanisms. CB1 agonists are unable to modulate protein synthesis or prevent the effect of rimonabant. Using C2C12 cells stably expressing an shRNA directed against CB1, or HEK293 cells overexpressing HA‐tagged CB1, we demonstrated that the effect of rimonabant is unaffected by CB1 expression level. In summary, rimonabant can stimulate protein synthesis in C2C12 myotubes through a CB1‐independent mechanism. These results highlight the need to identify non‐CB1 receptor(s) mediating the pro‐anabolic effect of rimonabant as potential targets for the treatment of sarcopenia, and to design new side‐effect‐free molecules that consolidate the effect of rimonabant on skeletal muscle protein synthesis. Abstract : Rimonabant prevents dexamethasone‐induced myotube atrophy without affecting proteolysis. Rimonabant stimulates protein synthesis in a time‐ and dose‐dependent manner through the mTOR pathway. Agonists or stable knockdown of CB1 receptor are unable to prevent the pro‐anabolic effect of rimonabant on protein synthesis.